2004
DOI: 10.1023/b:mcbi.0000007264.37170.39
|View full text |Cite
|
Sign up to set email alerts
|

The gender differences in health effects of environmental cadmium exposure and potential mechanisms

Abstract: On a viewpoint of gender differences in Cd body burden and its health effects, we reviewed the population-based research including our own which conducted in Japan, Thailand, Australia, Poland, Belgium and Sweden to assess health effects of human exposure to environmental cadmium and their potential mechanisms. As a result, six risk factors in Cd health effects in women have been identified; (1) more serious type of renal tubular dysfunction, (2) difference in calcium metabolism and its regulatory hormones, (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 27 publications
3
63
1
2
Order By: Relevance
“…Increased risk of death from ischemic heart disease, and increased incidence of diabetes and renal disease were seen in both men and women with signs of kidney effects, but excess risk of cancer of kidney, urinary tract, uterus, colon and rectum were seen in women only. More severe outcomes of Cd exposure in women than men have been noted in a previous report (Nishijo et al 2004). Increased risk of death among people showing signs of Cd kidney toxicity could be interpreted to suggest that that such kidney Cd toxicity may be an early warning of complications, sub-clinical or clinical morbidity.…”
Section: Cadmium and The Pathogenesis Of Hypertension In Humansmentioning
confidence: 67%
See 1 more Smart Citation
“…Increased risk of death from ischemic heart disease, and increased incidence of diabetes and renal disease were seen in both men and women with signs of kidney effects, but excess risk of cancer of kidney, urinary tract, uterus, colon and rectum were seen in women only. More severe outcomes of Cd exposure in women than men have been noted in a previous report (Nishijo et al 2004). Increased risk of death among people showing signs of Cd kidney toxicity could be interpreted to suggest that that such kidney Cd toxicity may be an early warning of complications, sub-clinical or clinical morbidity.…”
Section: Cadmium and The Pathogenesis Of Hypertension In Humansmentioning
confidence: 67%
“…Impaired tubular reabsorption of glucose has been noted in high-dose exposure situations (Nishijo et al 2004;Honda et al 2010). Such increased urinary glucose excretion may be indicative of mitochondrial toxicity of Cd in proximal tubular cells, affecting oxidative phosphorylation and ATP output (Gobe and Crane, 2010).…”
Section: Impaired Glucose Reabsorptionmentioning
confidence: 99%
“…One of them could be low body iron stores that increase Cd absorption [36]. There is also evidence for increased sensitivity to Cd toxicities in women [37].…”
Section: Resultsmentioning
confidence: 99%
“…For a half century, it had been known that women may be more affected by cadmium than men [14,21]. Recently, experimental studies suggested that cadmium effects on serum levels of calciotropic hormones and disorders in calcium and phosphate metabolism were higher in female than in male rats [12].…”
Section: Discussionmentioning
confidence: 99%